Variable contribution - dataframe - Radinger, Johannes; Wolter, Christian; Kail, Jochem (Dryad Digital Repository, 2015)
R-dataframe storing the contribution of single variables for each of the final BRT models. The dataframe is stored as R object in the *.rds format and can be loaded with the R command readRDS().